Clinical-epidemiological analysis of HIV positive patients hospitalized in a Burn Therapy Unit - Secanho, Murilo Sgarbi [UNESP]; De Menezes Neto, Balduino Ferreira [UNESP]; De Oliveira, Ana Beatriz Pedroso Maciel [UNESP]; Chequim, Merimar Maria [UNESP]; Carvalho, Laisa Brandão [UNESP]; Moragas, Weber Ribolli [UNESP]; Rocha, Cristiane; Palhares, Aristides Augusto [UNESP] (Thieme, 2022)
■ ABSTRACT Introduction: HIV infection and burns are common public health issues, especially in low-and middle-income countries. There is a paucity in the literature evaluating the epidemiology of burns hospitalization in HIV patients. This study aims to evaluate the clinical and epidemiological profile of HIV-positive patients hospitalized in a Burn Therapy Unit. Methods: A retrospective analysis of burn patients diagnosed with HIV was performed at the Therapy Unit of the State Hospital of Bauru between 2008 and 2018. Results: 2,364 medical records were reviewed, and 14 (0.6%) patients were diagnosed with HIV. The mean age was 43.1 years. Regarding gender, nine (64.3%) were male, and five (35.7%) were female. The most common mechanism was direct flame in 11 (78.7%) cases. The etiology was alcohol (42.9%) in six patients, in three explosions (21. 5%), and the others were gasoline, cigarettes and contact with exhaustion, all with one (7.1%) case. When the cause of these burns was evaluated, nine (64.3%) were due to accidents, either at work or home, two (14.3%) for attempted murder, one (7.1%) self-extermination, and two (14.3%) cases had no information. Regarding total burn surface area, five (37.5%) had burns of 0-10%, three (21.4%) 11-20% and five (35.7%) greater than 20%, and one was unknown. Four (28.6%) showed airway lesions. Two (14.3%) patients died. Conclusion: The prevalence of burned HIV-positive patients admitted to a specialized unit for this treatment is like the national one, with similar characteristics concerning age and gender.
Análise clínico-epidemiológica de pacientes HIV positivos internados em uma Unidade de Terapia de Queimados
Keywords: Burn units; Burns; Epidemiology; HIV Infections; Prevalence; Public Health